1997
DOI: 10.1111/j.1365-2494.1997.tb02346.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and colonization of gaps in sown swards of grass and clover under different sward managements

Abstract: The effects of extensive sward management and patch size on the persistence and colonization of gaps in sown swards was examined by creating gaps of five different sizes (2·3, 7, 10, 14 and 19 cm in diameter) in four different sward treatments: a fertilized sward grazed to 4 cm, i.e. relatively intensive management, and three extensively managed unfertilized swards, which were not grazed or grazed to 4 cm or 8 cm. The swards were originally sown with ryegrass (Lolium perenne L.) and white clover (Trifolium rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…By contrast, in wet grassland, MILBERG (1993) concluded that the seed bank was the main source of seedlings emerging after gap creation but these seedlings contributed very little to the colonization, which was clearly dominated by vegetative regrowth. In our case and as reported from perennial grasslands elsewhere (RAPP & RABINOWITZ 1985, MILBERG 1993, KOTANEN 1997, MARIOTT et al 1997, rapid vegetative spread was also a characteristic trait of species present in gaps. The importance of this trait was not surprising considering the high proportion of species using this strategy in perennial grasslands (KLIMEŠ et al 1997, MACEK & LEPŠ 2003.…”
Section: Functional Traits Of the Regenerative Phasementioning
confidence: 54%
See 1 more Smart Citation
“…By contrast, in wet grassland, MILBERG (1993) concluded that the seed bank was the main source of seedlings emerging after gap creation but these seedlings contributed very little to the colonization, which was clearly dominated by vegetative regrowth. In our case and as reported from perennial grasslands elsewhere (RAPP & RABINOWITZ 1985, MILBERG 1993, KOTANEN 1997, MARIOTT et al 1997, rapid vegetative spread was also a characteristic trait of species present in gaps. The importance of this trait was not surprising considering the high proportion of species using this strategy in perennial grasslands (KLIMEŠ et al 1997, MACEK & LEPŠ 2003.…”
Section: Functional Traits Of the Regenerative Phasementioning
confidence: 54%
“…Traits that provide advantages in a closed canopy are not necessarily an advantage for gap colonization. In perennials grasslands rapid vegetative spread (KOTANEN 1997, MARIOTT et al 1997) and smaller seed mass (KALAMEES & ZOBEL 2002, SUDING et al 2003 generally characterize gap colonizers. Consequently, plant species often occur with different relative frequencies in recently colonized gaps than they do in the surrounding vegetation (MARTINSEN et al 1990, BULLOCK et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…C'est ce qu'on observe lorsqu'il y a arrêt des entretiens de la peupleraie ; où les espèces, initialement herbacées, cèdent la place à des ligneux. La quantité de lumière, de moins en moins disponible au fur et à mesure du vieillissement d'une peupleraie, joue un rôle important dans l'établissement et la croissance des espèces végétales [32]. En raison des résultats obtenus en P1, ce modèle n'est pas en liaison avec les observations d'Odum [33] qui indiquent que la plus forte diversité en espèces s'observe à des taux modérés de gradients physiques.…”
Section: Introductionunclassified
“…Dung and urine may also create gaps in the canopy (Lantinga, 1986), especially under high stocking rates (Wolton, 1978). Small-and medium-sized gaps in the canopy are rapidly filled by vegetative expansion or seedlings (Marriott et al, 1997). Therefore, the dynamics of heterogeneity should be incorporated in a sward quality assessment, and this requires repeated measurements during the growing season.…”
Section: Assessment Of Sward Quality With Image Parametersmentioning
confidence: 99%
“…Keuning and Vellinga, 1986;Deenen, 1994). Local tiller or plant death creates gaps which may be filled with weeds (Keuning and Vellinga, 1986;Marriott et al, 1997). This leads to heterogeneous swards in terms of DM yield and feeding quality.…”
Section: Introductionmentioning
confidence: 99%